2012
DOI: 10.1074/mcp.m111.015313
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Interactome of HIV-1 Rev Includes RNA Helicases Involved in Multiple Facets of Virus Production

Abstract: The HIV-1 Rev protein plays a key role in the late phase of virus replication. It binds to the Rev Response Element found in underspliced HIV mRNAs, and drives their nuclear export by the CRM1 receptor pathway. Moreover, mounting evidence suggests that Rev has additional functions in viral replication. Here we employed proteomics and statistical analysis to identify candidate host cell factors that interact with Rev. For this we studied Rev complexes assembled in vitro with nuclear or cytosolic extracts under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
127
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 56 publications
7
127
0
1
Order By: Relevance
“…31 Our results support such a model in the control of vRNA encapsidation that involves subtle changes to the composition and trafficking of the HIV-1 RNP. hnRNP A2/B1 is a common component of several relevant HIV-1 complexes that have been recently characterized at the proteomics level 9,33,65 and these hnRNPs likely exert functions during the transit of HIV-1 complexes from the nucleus to and within the cytoplasm, perhaps acting in concert with Rev at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Our results support such a model in the control of vRNA encapsidation that involves subtle changes to the composition and trafficking of the HIV-1 RNP. hnRNP A2/B1 is a common component of several relevant HIV-1 complexes that have been recently characterized at the proteomics level 9,33,65 and these hnRNPs likely exert functions during the transit of HIV-1 complexes from the nucleus to and within the cytoplasm, perhaps acting in concert with Rev at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Several host proteins have been shown to influence Rev's activity by direct interaction or by influencing the ribonucleoprotein (RNP) context of the RNA. [9][10][11][12] Rev also has effects on splicing regulation 13,14 as well as on downstream gene expression events at the translation level. [15][16][17] Efforts to understand Rev's functions during viral replication cycle have provided several key leads in the identification of potential therapeutic strategies and targets 18,19 and have provided critical information on the processes governing nuclear RNA export in general.…”
Section: Introductionmentioning
confidence: 99%
“…We initially identified NonO interacting with PICs in HIV-1-infected CD4 + T cell lines, 9 and subsequent studies have also identified NonO to be an HIV-1 interactant. [10][11][12] However, the significance of these interactions and whether NonO plays a crucial role in HIV-1 infection have not been answered. We addressed these questions by investigating the effect of NonO KD on HIV-1 infection and characterized what stages of the replication cycle were affected.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, NonO was identified in an analysis of the Rev interactome in HeLa cells, and the association between NonO and Rev was enhanced by the presence of the Rev response element. 12 These studies suggest that NonO may affect multiple steps of the HIV-1 lifecycle including integration. However, the role of NonO in HIV-1 infection has not been clearly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has identified cellular proteins by direct and indirect interactions with Rev that facilitate transport of RRE-containing viral mRNA out of the nucleus [34,[42][43][44]. We had shown that a mutant Tat protein, we call Nullbasic, has an intriguing ability to inhibit Rev function resulting from its mislocalization from the nucleolus to the nucleoplasm and cytoplasm.…”
Section: Discussionmentioning
confidence: 99%